Helmets and Mouth Guards: The Role of Personal Equipment in Preventing Sport-Related Concussions - Daneshvar, Daniel H. (2011)
Every year, millions of athletes in the United States experience concussions. With athletes at all levels of play getting bigger, faster, and stronger, it has been suggested that newer technologies may provide an opportunity to reduce the risk and severity of these all too frequent injuries. Although helmets have been shown to decrease the rate of catastrophic head injuries, and mouth guards have decreased the risk of dental and oral injuries, the protective effect of helmets and mouth guards on concussions has not been conclusively demonstrated. In this review, the current literature pertaining to the effect that equipment has on concussions is evaluated. Understanding the role that this equipment plays in preventing concussions is complicated by many factors, such as selection bias in non-randomized studies, variations in playing style, and risk compensation in sports with mandatory protective equipment. At this point, there is little evidence supporting the use of specific helmets or mouth guards to prevent concussions outside of specific sports such as cycling, skiing, and snowboarding. Improving coach and player education about proper concussion management, encouraging neck strengthening exercises, and minimizing high-risk impacts may provide a more fruitful avenue to reduce concussions in sports.